The Role of Business Incubators in Encouraging the Growth of Creative Entrepreneurs in Indonesia - Ilham Teruna Bakti; Pudji Astuty (Pelopor Publikasi Akademika, 2026)
Business incubators have emerged as strategic instruments in developing Indonesia's creative entrepreneurship ecosystem. This study examines the role of business incubators in accelerating the growth of creative entrepreneurs, with a focus on their contributions to the creative economy sector, which contributed 7.8% to GDP (IDR 1.05 trillion) in 2023 and has grown the number of technology business incubators to 150 institutions in the past five years. Using a qualitative approach with secondary data analysis from official sources including the Ministry of Industry, the Coordinating Ministry for Economic Affairs, the Central Statistics Agency, and business incubator reports, this research identified that business incubators contribute significantly through access to capital, management coaching, network development, and enhanced digital technology capabilities. The findings reveal that the Creative Business Incubator program successfully increased participants' turnover and expanded market access both domestically and for exports, while digital incubation models have improved accessibility and scalability for creative entrepreneurs across Indonesia. This study concludes that business incubators play a strategic role in unlocking the creative economy's potential by transforming creative ideas into viable business models through the triple helix synergy between government, universities, and the private sector, recommending strengthened stakeholder collaboration and the development of incubation models adaptive to the dynamics of the creative industry in the digital era to achieve the national entrepreneurship ratio target of 3.95% by 2024.